HUBUNGAN ANTARA SUPERVISI KLINIS, KOMPETENSI PEDAGOGIK GURU DENGAN KINERJA GURU DI SMPN SE KECAMATAN PINANG RAYA KABUPATEN BENGKULU UTARA - Ariani Maimunah; Rohiat Rohiat; Aliman Aliman (Manajer Pendididikan, 2018)
Abstract: The purpose of this research was determine and analyze the relationship of clinical supervision, pedagogic competence of teachers with the performance of teachers in the learning process at junior high school in Pinang Raya subdistrict, North Bengkulu Regency. This research is a correlational research with quantitative approach, by using questionnaire which is distributed to 53 sample of teachers at SMPN se Pinang Raya Sub-district, North Bengkulu Regency. Data analyzed with correlation method to determine relationship between variables. The results showed that 1) there was a positive significant correlation on clinical supervision with teacher performance in the learning process in view from regression analysis with t test value of 43,574> 2,007 (t table 0,05 = 2,007) with r correlation equal to 0,987 into category a very strong relationship. 2) there was a positive significant correlation on pedagogic competence with teacher performance in learning process seen from result of regression analysis with t test value 13,489 > 2,007 (t table 0,05 = 2,007) with r correlation equal to 0,884 enter goes to strong relationship category 3 ) there was positive significant correlation on clinical supervision, pedagogic competence together with teacher performance in learning process seen from result of regression analysis with t test value 19,398 > 2,007 and 2,966 > 2,007 (t table 0,05 = 2,007) with r correlation equal to 0,987 goes to a very strong relationship category. The conclusion of this research is there is very strong relationship on clinical supervision, pedagogic competence with teacher performance at junior high school on Pinang Raya Subdistrict North Bengkulu Regency. Keywords: Clinical supervision, Pedagogic competence, Teacher performance